Paravertebral Catheter Placement, Under Direct Vision, for Postthoracotomy Analgesia. Issue 6 (December 2015) - Brown, Tristam; D'Netto, Trevor J.; Falk, Gregory L.; Phillips, Stephanie
Abstract : Supplemental Digital Content is available in the text.